Predictors of traumatic birth experience among a group of Iranian primipara women: a cross sectional study - Ghanbari-Homayi, Solmaz (BMC Pregnancy Childbirth, 2019)
BACKGROUND: Traumatic birth experience has undesirable effects on the life of the mother, child, family, and society. The identification of predictive factors can be useful in improving birth experiences among women. This study aimed to assess the prevalence of a traumatic birth experience and identify its predictors among a group primiparous women. METHODS: A cross-sectional study was conducted among 64 health centres in Tabriz, the second largest city in Iran. Cluster sampling was used to recruit 800 eligible women at one to 4 months postpartum. The Persian version of the Childbirth Experience Questionnaire was used to measure the womens’ birth experiences. Data were collected through face to face interviews and analysed mainly by multivariable logistic regression. RESULTS: The prevalence of traumatic birth experience was 37% in the study group. The independent predictors of the traumatic birth experience were related to antenatal and intrapartum factors. The antenatal predictor was the lack of exercise during pregnancy (OR = 2.81, CI 1.40–5.63, P = .003) and the intrapartum predictors were the absence of pain relief during labour and birth (OR = 4.24, CI 2.12–8.50, P < .001), and the fear of childbirth (OR = 3.47, CI 1.68–7.19, P < .001). CONCLUSIONS: The findings revealed the high rate of traumatic birth experience among the primimarous women and identified the importance of a woman-centered care where a woman can actively make decision about the care she receives receive during labour and birth. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12884-019-2333-4) contains supplementary material, which is available to authorized users.